Calotropis Gigantea Fiber-epoxy Composites: Influence of Fiber Orientation on Mechanical Properties and Thermal Behavior. Issue 10 (3rd October 2022) - Ramesh, G.; Subramanian, K.; Sathiyamurthy, S.; Prakash, M.
ABSTRACT: Global warming and environmental pollution issues are the challenges that have prompted researchers around the world to recognize biodegradable material as an alternate solution for fossil fuel dependency. The previous literature motivates the researchers to identify alternatives to artificial reinforcement in composite materials. This work utilizes Calotropis gigantea fiber as a strengthening agent, which is generously available as an unused plant in India. Compression molding technique was used for the preparation of specimens with different fiber orientation (0°, 15°, 30°, 45°, 60°, 75°, 90°, 0°/90°, and 0°/45°/90°) Specimen with 0° fiber orientation registered a maximum value of 142.46 MPa, 93.13MPa, and 81.21 kJ/m 2 in Flexural test, Tensile test and Impact test, respectively, than the other orientations. Mechanical testing results establish that the orientation of the fiber will prominently influence in improving the strength. The thermal studies on Calotropis gigantea fiber-epoxy composites through Thermogravimetric Analysis and Differential Scanning Calorimetry reveal that the composite will withstand more than 600°C temperature and confirm its thermal stability. The combined findings show that Calotropis gigantea fiber in polymer composite can be a possible reinforcing material and suitable for manufacturing accessories for automobile and household applications.